Assessment of Recording Bias in Pregnancy Studies using Health Care Databases: An application to neurologic conditions - MacDonald, Sarah C (Paediatr Perinat Epidemiol, 2018)
BACKGROUND: Pre-existing conditions are imperfectly recorded in healthcare databases. We assessed whether pre-existing neurologic conditions (epilepsy, multiple sclerosis [MS]) were differentially recorded in the presence of major obstetric outcomes (Caesarean delivery, preterm delivery, preeclampsia) in delivery records. We also evaluated the impact of differential recording on measures of frequency and association between the conditions and outcomes. METHODS: The 2011-2014 Truven Health MarketScan® Commercial Claims Dataset was used to identify deliveries. We calculated the relative recording of epilepsy and MS at delivery compared with a 270-day pre-delivery interval, both overall and by the presence of major obstetric outcomes. We estimated risk ratios of the association between epilepsy and MS with the outcomes for each ascertainment window. RESULTS: We identified 909,065 deliveries in women continuously enrolled from 270-days before the delivery date. Of women with epilepsy identified in the pre-delivery interval, 73% had the condition coded at delivery. For MS, the proportion was 60%. MS recording at delivery did not vary by obstetric outcomes, however delivery-coded epilepsy was less likely confirmed in the pre-delivery interval in the presence of preeclampsia. Generally, the period of ascertainment did not meaningfully impact risk ratios, however the risk ratio for preeclampsia associated with epilepsy was 1.67 [95% CI: 1.47, 1.90] when epilepsy was ascertained at delivery and 1.26 [95% CI: 1.07, 1.48] when epilepsy was ascertained in the pre-delivery interval (heterogeneity, p=0.007). CONCLUSIONS: Ascertainment of epilepsy and MS in delivery records underestimated prevalence. However the window of recording generally did not impact associations with obstetric outcomes.